Develop the Speech of Primary Class Students Modern Issues - Kholdarova Iroda Valizhonovna; Alijonova Malikakhan (Genius Journals, 2023)
In this article, the methodology of speech development in elementary school classes, oral and written speech, their interrelationship, specific characteristics, and the reasons for the shortcomings in the speech of students in the development of oral speech , ways to eliminate it, communication skills that should be formed in students by achieving speech development in the process of quality education are discussed.
Keywords: speech; methodology; aspects of speech; speech therapist